Estimation of the climate mitigation effects of hypothetical greening scenarios in Kyoto City with the regional meteorological model WRF - Asahi Ueda; Ryo Nukina; Junichi Imanishi (Landscape and Ecological Engineering, 2026)

Correlations between white matter hyperintensities, magnetic resonance imaging findings, and cognition in the oldest old: a multimodal cross-sectional study - Ryo Ueda; Ryo Shikimoto; Jinichi Hirano; Takashi Sasaki; Yukiko Abe; Masaru Mimura; Yasumichi Arai (GeroScience, 2026)

TTNOpt: Tree tensor network package for high-rank tensor compression - Ryo Watanabe; Hidetaka Manabe; Toshiya Hikihara; Hiroshi Ueda (Computer Physics Communications, 2026)

Modern silica sinter deposits from an island-arc setting and their potential for fossilizing plants - Aya Kubota; Ryo Taniguchi; Tomoyuki Ueda; Yasuhiro Iba (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Intraoperative Language mapping in a Japanese-English-French trilingual patient with a left Temporal lobe glioma: a case report - Kosei Yamamoto; Ryota Tamura; Sara Ganaha; Kosuke Karatsu; Tomoko Ishizawa; Kazuhiro Kojima; Makiko Ando; Kenzo Kosugi; Yohei Kitamura; Ryo Ueda; Aiko Ishikawa; Tomoyuki Imanishi; et al. (Brain Structure and Function, 2025)

Longitudinal structuring of stream-fish assemblages: is niche partitioning observed in two-species systems applicable to three-species systems? - Kentaro Morita; Jun-ichi Tsuboi; Genki Sahashi; Ryo Futamura; Kazutoshi Ueda; Mari Kuroki (Ichthyological Research, 2024)
Longitudinal distribution and niche partitioning phenomena have been extensively reported for streams containing two salmonid species but remain poorly understood for streams containing three or more salmonid species. Herein, we examined the abiotic environmental variables and population densities of fishes, including three salmonids, in 30 reaches of the Setose River, Hokkaido, Japan, across altitudes (120–450 m) and maximum water temperature (15–26 °C) gradients to determine the distribution of major fish species in this system. The densities of white-spotted charr Salvelinus leucomaenis , southern Asian Dolly Varden Salvelinus curilus , masu salmon Oncorhynchus masou , fluvial sculpin Cottus nozawae , and stone loach Barbatula oreas varied along environmental gradients despite their wide distribution sympatrically. We further investigated the interspecific interactions between three potentially competitive salmonids, white-spotted charr, Dolly Varden, and masu salmon. We observed that in the three-species system, including upstream Dolly Varden, salmon occupied upstream areas colder than those inhabited by charr, which is contrary to the pattern reported for charr and salmon two-species systems, wherein charr are found in the colder upstream areas. In underwater observations, salmon preferred faster water velocities than charr and Dolly Varden. Dolly Varden were found exclusively on the riverbed, followed by charr, whereas salmon occurred further away from the riverbed. Analysis of the stomach contents revealed that all three salmonids depended on terrestrial insects, but only Dolly Varden consumed benthic aquatic insects. In our three-species system that included Dolly Varden (preadapted to benthos foraging), no difference was observed in the degree of terrestrial insect consumption between charr and salmon. These results are in striking contrast to the reports of charr preying on relatively more aquatic insects than those consumed by salmon in charr and salmon two-species systems. Therefore, we speculate that Dolly Varden and salmon influence interspecific interactions between charr and salmon and between charr and Dolly Varden, respectively, explaining the distinct longitudinal distribution and feeding habits observed in two- vs. three-species systems. These variant interspecific interactions among the three competing species may have driven the expansion of their sympatric zones.

Japanese Planocerid Flatworms: Difference in Composition of Tetrodotoxin and Its Analogs and the Effects of Ingestion by Toxin-Bearing Fishes in the Ryukyu Islands, Japan - Hiroyuki Ueda; Masaaki Ito; Ryo Yonezawa; Kentaro Hayashi; Taiga Tomonou; Maho Kashitani; Hikaru Oyama; Kyoko Shirai; Rei Suo; Kazutoshi Yoshitake; Shigeharu Kinoshita; Shuichi Asakawa; et al. (Marine Biotechnology, 2024)
Tetrodotoxin (TTX), known as pufferfish toxin, is a potent neurotoxin blocking sodium channels in muscle and nerve tissues. TTX has been detected in various taxa other than pufferfish, including marine polyclad flatworms, suggesting that pufferfish toxin accumulates in fish bodies via food webs. The composition of TTX and its analogs in the flatworm Planocera multitentaculata was identical to those in wild grass puffer Takifugu alboplumbeus . Previously, Planocera sp. from Okinawa Island, Japan, were reported to possess high level of TTX, but no information was available on TTX analogs in this species. Here we identified TTX and analogs in the planocerid flatworm using high-resolution liquid chromatography–mass spectrometry, and compared the composition of TTX and analogs with those of another toxic and non-toxic planocerid species. We show that the composition of TTX and several analogs, such as 5,6,11-trideoxyTTX, dideoxyTTXs, deoxyTTXs, and 11-norTTX-6( S )-ol, of Planocera sp. was identical to those of toxic species, but not to its non-toxic counterpart. The difference in the toxin composition was reflected in the phylogenetic relationship based on the mitochondrial genome sequence. A toxification experiment using predatory fish and egg plates of P. multitentaculata demonstrated that the composition of TTX and analogs in wild T. alboplumbeus juveniles was reproduced in artificially toxified pufferfish. Additionally, feeding on the flatworm egg plates enhanced the signal intensities of all TTX compounds in Chelonodon patoca and that of deoxyTTXs in Yongeichthys criniger .

Rendezvous trajectory design of logistics resupply missions to the lunar gateway in near-rectilinear halo orbit - Ryo Nakamura; Junji Kikuchi; Takahiro Sasaki; Yuki Matsumoto; Moeko Hidaka; Naomi Murakami; Satoshi Ueda; Naoki Satoh (Journal of Space Safety Engineering, 2023)

White matter changes follow low-frequency repetitive transcranial magnetic stimulation plus intensive occupational therapy for motor paralysis after stroke: a DTI study using TBSS - Ryo Ueda; Naoki Yamada; Masahiro Abo; Atsushi Senoo (Acta Neurologica Belgica, 2021)

Forced response and internal variability of summer climate over western North America - Youichi Kamae; Hideo Shiogama; Yukiko Imada; Masato Mori; Osamu Arakawa; Ryo Mizuta; Kohei Yoshida; Chiharu Takahashi; Miki Arai; Masayoshi Ishii; Masahiro Watanabe; Masahide Kimoto; et al. (Climate Dynamics, 2017)

Interaction Between Titanium and Cadmium in Various Guinea Pig Organs - Takashi Takano; Takeharu Kaneda; Masaki Kaneshige; Tomoko Tsutsumi; Yoshitsugu Ochiai; Kazumasa Shimizu; Ryo Hondo; Mariko Mochizuki; Fukiko Ueda (Biological Trace Element Research, 2013)

The Distribution of Several Elements in Cat Urine and the Relation Between the Content of Elements and Urolithiasis - Mariko Mochizuki; Misato Morikawa; Takuya Yogo; Kimiyo Urano; Katsumi Ishioka; Minoru Kishi; Ryo Hondo; Fukiko Ueda; Toshinori Sako; Fujiro Sakurai; Norio Yumoto; Masahiro Tagawa (Biological Trace Element Research, 2011)

A Basic Study on the Biological Monitoring for Vanadium—Effects of Vanadium on Vero Cells and the Evaluation of Intracellular Vanadium Contents - Mariko Mochizuki; Eiko Kudo; Mitsuho Kikuchi; Takashi Takano; Yojiro Taniuchi; Tomoya Kitamura; Ryo Hondo; Fukiko Ueda (Biological Trace Element Research, 2011)

Photosynthetic responses of birch and alder saplings grown in a free air CO2 enrichment system in northern Japan - Norikazu Eguchi; Kazuki Karatsu; Tatsushiro Ueda; Ryo Funada; Kentaro Takagi; Tsutom Hiura; Kaichiro Sasa; Takayoshi Koike (Trees, 2008)

A new index for evaluation of cadmium pollution in birds and mammals - Mariko Mochizuki; Makoto Mori; Ryo Hondo; Fukiko Ueda (Environmental Monitoring and Assessment, 2008)

Production of Transgenic-clone Pigs by the Combination of ICSI-mediated Gene Transfer with Somatic Cell Nuclear Transfer - Mayuko Kurome; Hideto Ueda; Ryo Tomii; Katsutoshi Naruse; Hiroshi Nagashima (Transgenic Research, 2006)

The Distribution of Molybdenum in the Tissues of Wild Ducks - Mariko Mochizuki; Rei Sasaki; Yuko Yamashita; Mayumi Akinaga; Nana Anan; Sakura Sasaki; Ryo Hondo; Fukiko Ueda (Environmental Monitoring and Assessment, 2002)

Cadmium Contamination in Wild Birds as an Indicator of Environmental Pollution - Mariko Mochizuki; Ryo Hondo; Kiichi Kumon; Rei Sasaki; Hironori Matsuba; Fukiko Ueda (Environmental Monitoring and Assessment, 2002)